2021
DOI: 10.3389/fonc.2021.801173
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Detection of Pancreatic Cancer Through Liquid Biopsy

Abstract: Pancreatic cancer refers to the development of malignant tumors in the pancreas: it is associated with high mortality rates and mostly goes undetected in its early stages for lack of symptoms. Currently, surgical treatment is the only effective way to improve the survival of pancreatic cancer patients. Therefore, it is crucial to diagnose the disease as early as possible in order to improve the survival rate of patients with pancreatic cancer. Liquid biopsy is a unique in vitro diagnostic technique offering th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 97 publications
(121 reference statements)
0
1
0
Order By: Relevance
“…A number of recent studies have demonstrated the potential of liquid biopsy for cancer screening, refinement of diagnosis, and early of cancer recurrences [43,61]. By detecting circulating tumor cells, nucleic acids, and exosomes, the method can be used for early cancer detection, diagnosis, and prognosis in various types of cancer [35,63,71,149]. Additionally, liquid biopsy can provide insights into cancer progression and treatment response by assessing cancer cachexia, muscle-derived microRNAs, and energy metabolism [16].…”
Section: Early Detection and Diagnosismentioning
confidence: 99%
“…A number of recent studies have demonstrated the potential of liquid biopsy for cancer screening, refinement of diagnosis, and early of cancer recurrences [43,61]. By detecting circulating tumor cells, nucleic acids, and exosomes, the method can be used for early cancer detection, diagnosis, and prognosis in various types of cancer [35,63,71,149]. Additionally, liquid biopsy can provide insights into cancer progression and treatment response by assessing cancer cachexia, muscle-derived microRNAs, and energy metabolism [16].…”
Section: Early Detection and Diagnosismentioning
confidence: 99%
“…miRNAs are noncoding, single-stranded RNA molecules up to 22 nucleotides long that function as posttranscriptional gene expression regulators [40]. Various miRNAs have been utilized to differentiate PDAC patients from those with benign lesions, CP, and healthy controls, and a JAMA-published study reported 38 significantly dysregulated miRNAs in PDAC patients compared to controls [41].…”
Section: Mirnasmentioning
confidence: 99%
“…Life 2022, 12, 327 2 of 16 Recently, advances have been made to detect metastatic pancreatic ductal adenocarcinoma (PDAC) using molecular magnetic resonance imaging (MMRI) [14]. Additionally, advances have been made in liquid biopsy [15] and in finding specific biomolecular or subcellular targets [16][17][18][19], new therapeutic agents [20], and nanomedicine applications [21][22][23][24][25][26][27][28]. Moreover, our understanding of the molecular biology events of pancreatic cancer cells has increased [29][30][31].…”
Section: Introductionmentioning
confidence: 99%